2020
DOI: 10.1155/2020/2304173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assessment of Resistance to Clarithromycin in Helicobacter pylori Strains Isolated from Patients with Dyspepsia by Fluorescent In Situ Hybridization in the Center of Iran

Abstract: Background and Aims. Helicobacter pylori is a common infectious bacterium mostly found in gastroduodenal diseases. The increased prevalence of clarithromycin-resistant H. pylori strains is a major challenge in the successful treatment of infections caused by this organism. The present study is aimed at detecting the clarithromycin resistance pattern of H. pylori strains isolated from gastric biopsies and evaluating point mutations of the 23S rRNA gene. Patients and methods. In the present descriptive cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…3 The most frequent and well-studied molecular pathway for clarithromycin resistance is due to A2142G and A2143G point mutations in domain V of the 23S rRNA gene. 4 Other mutations like A2142C, G1939A, A2115G, G2141A, A2144G, A2144T, C2147G, T2182C, G2224A, and T2215C vary geographically and found to mediate resistance phenotype. 1,3,5 This study on the characterization of 23S rRNA gene mutations in clinical isolates of H. pylori in Pakistan found three new features of domain V. First, a new MboII RFLP pattern was found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The most frequent and well-studied molecular pathway for clarithromycin resistance is due to A2142G and A2143G point mutations in domain V of the 23S rRNA gene. 4 Other mutations like A2142C, G1939A, A2115G, G2141A, A2144G, A2144T, C2147G, T2182C, G2224A, and T2215C vary geographically and found to mediate resistance phenotype. 1,3,5 This study on the characterization of 23S rRNA gene mutations in clinical isolates of H. pylori in Pakistan found three new features of domain V. First, a new MboII RFLP pattern was found.…”
Section: Introductionmentioning
confidence: 99%
“… 3 The most frequent and well-studied molecular pathway for clarithromycin resistance is due to A2142G and A2143G point mutations in domain V of the 23S rRNA gene. 4 Other mutations like A2142C, G1939A, A2115G, G2141A, A2144G, A2144T, C2147G, T2182C, G2224A, and T2215C vary geographically and found to mediate resistance phenotype. 1 , 3 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…This has a blocking effect on the link between the antibiotic and the ribosome, and consequently, protein synthesis is not inhibited by the drug. Furthermore, mutations have also been found in A2143G, A2144G, A2143C, and T2182C, which cause resistance to clarithromycin in H. pylori strains [130,131].…”
Section: The Diagnosis Over Timementioning
confidence: 99%
“…The first study in 1990 confirmed that the cure for duodenal ulcer will be healing from the H. pylori infection, and in 1992, trials for proposed vaccines started. In 1994, the first trials with PPI triple therapies for ulcer treatment began; in 1996, the Maastricht I Consensus Report (and later, the other report), screen-and-treat strategy was proposed over time, and in 2010, the bismuth quadruple therapies were revisited [23,24,130]. All patients with gastric or duodenal ulcers who are positive for H. pylori should receive primary treatment for the eradication of the bacterium, which is based on a proton pump inhibitor and is given in combination with two antibiotics for 7 days.…”
Section: New Therapeutic Issuesmentioning
confidence: 99%
“…A culture-based method is difficult as H pylori is a fastidious organism capable of growing only under a narrow set of conditions. Resistance to clarithromycin of H pylori was associated with point mutations of the V domain of the 23S rRNA gene in the 50S subunit that decreases the affinity of drug binding to the ribosome, 22 and PCR-RFLP method has been developed to detect these point mutations. PCR-RFLP method has expressed a reliable assay allowing cost-effective and rapid detection of clarithromycin-resistant strains.…”
Section: Number Of Patients Percentmentioning
confidence: 99%